White Paper: Radiology Curriculum for Undergraduate Medical Education in Germany and Integration into the NKLM 2.0 - Dettmer, Sabine; Barkhausen, Jörg; Volmer, Erik; Mentzel, Hans-Joachim; Reinartz, Sebastian; Voigt, Florian; Wacker, Frank K.; Baeßler, Bettina; Konferenz der Lehrstuhlinhaber für Radiologie (KLR); Adam, G.; Antoch, G.; Attenberger, U.; Bamberg, F.; Barkhausen, J.; Beer, M.; Bley, T.; Bücker, A.; Denecke, T.; Düber, C.; Forsting, M.; Hamm, B.; Heindel, W.; Hoffmann, R.-T.; Hosten, N.; Jansen, O.; Kauczor, H. U.; Krombach, G.; Kröncke, T. J.; Kuhl, C.; Lotz, J.; Mahnken, A.; Maintz, D.; Makowski, M.; Nikolaou, K.; Pech, M.; Ricke, J.; Rummeny, E.; Schönberg, S.; Schreyer, A.; Stroszczynski, C.; Teichgräber, U.; Uder, M.; Vogl, T.; Wacker, F.; Weber, M.-A.; Wohlgemuth, W.; Vorstand der Deutschen Röntgengesellschaft (DRG); Antoch, G.; Anton, F.; Barkhausen, J.; Dörfler, A.; Körber, F.; Layer, G.; Neumann, S.; Schönberg, S.; Vogl, T.; Wessling, J.; Wucherer, M.; Vorstandskommission der AG Lehre der DRG; Barkhausen, J.; Afat, S.; Baeßler, B.; Bamberg, F.; Dettmer, S.; Frisch, A.; Goldschmidt, O.; Hansen, N. L.; Hattingen, E.; Maintz, D.; Mentzel, H. J.; Molwitz, I.; Müller-Peltzer, K.; Pinto dos Santos, D.; Reinartz, S.; Rengier, F.; Teichgräber, U.; Vogl, T. J.; Völker, M.; Weis, M. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Objective The aim was to develop a new curriculum for radiology in medical studies, to reach a national consensus and to integrate it into the new national competence-based learning objectives catalog (NKLM 2.0). In this statement of the German Radiological Society (DRG), the process of curriculum development is described and the new curriculum is presented together with suggestions for practical implementation.Materials and Methods The DRG has developed a new curriculum for radiology. This was coordinated nationally among faculty via an online survey and the result was incorporated into the NKLM 2.0. Furthermore, possibilities for the practical implementation of the competency-based content are shown and different teaching concepts are presented.Results The developed curriculum is competency-based and aims to provide students with important skills and abilities for their future medical practice. The general part of the curriculum is divided into the topics “Radiation Protection”, “Radiological Methods” and radiologically-relevant “Digital Skills”. Furthermore, there is a special part on the individual organ systems and the specific diseases. In order to implement this in a resource-saving way, new innovative teaching concepts are needed that combine the advantages of face-to-face teaching in small groups for practical and case-based learning with digital teaching offers for resource-saving teaching of theoretical content.Conclusion We have created a uniform radiology curriculum for medical studies in Germany, coordinated it nationally and integrated it into the NKLM 2.0. The curriculum forms the basis of a uniform mandatory radiology teaching and should be the basis for the individual curriculum development of each faculty and strengthen the position of radiology in the interdisciplinary context.Key Points: Citation FormatZiel Ziel war es, ein neues Curriculum für die Radiologie im Medizinstudium zu entwickeln, national zu konsentieren und in den neuen nationalen kompetenzbasierten Lernzielkatalog (NKLM 2.0) zu integrieren. In diesem Artikel soll als ein Statement der Deutschen Röntgengesellschaft (DRG) der Prozess der Curriculumentwicklung beschrieben und das neue Curriculum zusammen mit Vorschlägen zur praktischen Umsetzung vorgestellt werden.Material und Methoden Die DRG hat ein neues Curriculum für die Radiologie erarbeitet. Dieses wurde mittels einer Online-Umfrage national unter den Lehrverantwortlichen abgestimmt und das Ergebnis in den NKLM 2.0 eingebracht. Des Weiteren werden Möglichkeiten der praktischen Umsetzung der kompetenzbasierten Inhalte aufgezeigt und verschiedene Lehrkonzepte vorgestellt.Ergebnisse Das erarbeitete Curriculum ist kompetenzbasiert und soll den Studierenden wichtige Fähigkeiten und Fertigkeiten für ihre spätere ärztliche Tätigkeit vermitteln. Der allgemeine Teil des Curriculums gliedert sich in die Themen „Strahlenschutz“, „Radiologische Methoden“ und radiologisch relevante „Digitale Kompetenzen“. Des Weiteren gibt es einen speziellen Teil zu den einzelnen Organsystemen und den spezifischen Krankheitsbildern. Um dies ressourcensparend umzusetzen, sind neue innovative Lehrkonzepte nötig, die die Vorteile des Präsenzunterrichts in kleinen Gruppen zum praktischen und fallbasierten Lernen mit digitalen Lehrangeboten zur ressourcensparenden Vermittlung theoretischer Inhalte kombinieren.Schlussfolgerung Wir haben ein einheitliches radiologisches Curriculum für das Medizinstudium in Deutschland erstellt, national abgestimmt und in den NKLM 2.0 integriert. Das Curriculum bildet die Grundlage einer einheitlichen verpflichtenden radiologischen Lehre und soll Grundlage für die individuelle Lehrplanentwicklung der einzelnen Fakultäten sein sowie die Position der Radiologie im interdisziplinären Kontext stärken.Kernaussagen: Zitierweise
Keywords: undergraduate medical education; curriculum radiology; National Competency-based Learning Objectives Catalogue in Medicine; competency-based teaching; innovative teaching concepts; E-learning